Stability Enhancement of STATCOM using Flower Pollination Algorithm - Velpula, Srikanth; R, Thirumalaivasan; M, Janaki (International Journal of Engineering and Technology, 2018)
The Static Synchronous Compensator (STATCOM) is a Voltage Source Converter (VSC) based shunt connected FACTS device. The key roles of STATCOM are to control the voltage at midpoint of transmission line, enhance power transfer capability and control reactive power at load end. However, the performance of STATCOM depends upon the parameters of the controller. In this paper, we present the tuning of Type-1 controller parameters for STATCOM based on a systematic method using Flower Pollination Algorithm (FPA). The margins for the Type-1 controller parameters are estimated from the movement of eigenvalues for the variation in controller parameters during inductive and capacitive modes of STATCOM. The performance of the STATCOM with FPA optimized Type-1 controller parameters is evaluated by transient simulation. The eigenvalue analysis and transient simulation are done based on D-Q model of STATCOM. It is noticed that, the response of STATCOM follows the step change in reactive current reference with least error.Â Â